An overview of tools useful in the speech diagnosis of a child with intellectual disability - Szurek, Mateusz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Mateusz Szurek, An overview of tools useful in the speech diagnosis of a child with intellectual disability. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 223–248. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.11 Object literature offers standards of diagnostic procedure for oligophasia. The book market still lacks, however, tools that would be developed for the purpose of logopaedic diagnoses of persons with intellectual disabilities (ID), which could fully assess the speech of a child with oligophasia. Presently, specialists utilise tools used for diagnosing other disorders or create their own research tools. The choice of relevant diagnostic tools, and, as a result – later result analysis, is a complex process mostly due to the great variation of functioning of persons with ID, and due to the lack of developed reference norms for the population of persons with ID (conclusions on language development in this group are by and large quite general, frequently formulated intuitively and without support by empirical studies). As a result, the author concluded an analysis of diagnostic tools available on the book market that could provide aid in the logopaedic assessment of a child with ID, stressing the need to create an original tool adapted for diagnosing the speech disorder of oligophasia.